Peningkatan Pengetahuan Guru Tentang Upaya Pencegahan Penyakit Stroke - Apriani Apriani (IKesT Muhammadiyah Palembang, 2022)
Stroke is one of the diseases that ranks the highest cause of death in the world consisting of heart failure, diabetes, and respiratory disease. Disability experienced by stroke patients include the inability to walk, the inability to communicate, and the inability to self-care. Prevention of stroke was needed to reduce the incidence of stroke. Prevention efforts can be done if we know what risk factors cause stroke. The purpose of this activity was to increase knowledge of teacher about stroke prevention efforts at SDN 21 Gelumbang. The form of efforts to increase knowledge and prevention of stroke in teachers was by conducting health education. The method used in this community service was lectures and questions and answers by giving leaflets to 21 counseling participants. This community service was carried out at SDN 21 Gelumbang on December 16, 2021. The results obtained in this activity were an increase in teacher knowledge about stroke prevention efforts. The conclusion of this activity was there was an increase in teacher knowledge about the basic concepts of stroke, ranging from signs and symptoms, stroke risk factors, both primary and secondary stroke prevention.